Edge of intrinsic absorption of light in a quantized semiconductor wire - Ibadullaeva Z.Q; Eshpulatov B.E; Ubaydullaev M.Sh. (Global Scientific Publishing, 2023)
The Coulomb interaction of an electron and a hole in the plane of the cross section of a cylindrical wire into exciton states is considered. The energy spectrum of the Wannier-Mott exciton in a semiconductor wire in the presence of dimensional quantization is calculated. An expression is obtained and analyzed for the interband light absorption coefficient taking into account exciton effects. It is shown that the interaction of an electron and a hole leads to the appearance of new lines in the absorption spectrum.
Keywords: Coulomb interaction; exciton; electron